Development of Caregiver Capacity by Community Participation in Screening for Dementia among Older Persons - สุริยะ จิรานันท์; อึ้งวัฒนา ศิวพร; บุญเชียง วราภรณ์ (Nursing Journal CMU, 2019)
Dementia is a major public health problem for older people across the world. Therefore, the purpose of this study was to develop caregiver capacity in the community by enabling them to participate in screening for dementia in older people and, to study the possibility of creating a training program to develop caregiver capacity in the community for screening for dementia in older people. The sample size of this study was 57 people divided into two groups. The research had three phases which were 1) the situation analysis phase, 2) the operation phase, and 3) the evaluation phase. The first group of 27 people were in the situation analysis phase which included persons who have been involved in screening for dementia among older persons. The second group of 30 caregivers were in the operation phase and evaluation phase that included persons who have been involved in screening for dementia among older persons. This was the same as the first group and 30 caregivers. The research instruments were a vertical semi-structured interview questions and a questionnaire about the possibility of a training program for developing caregiver capacity through community participation in screening for dementia in older people. The reliability of the questionnaire was 0.92. The concept of community participation by Cohen and Uphoff (1980) was used as a model. The development of caregiver capacity by community participation in screening for dementia in older people have been a training program for community members who are screening for dementia in older people and the possibility of training program of developing the caregiver capacity by community participation in screening for dementia in older people were easy to use, appropriate to apply, save time and money and the clarity and understanding were very good. These result show that a training program for community members who are screening for dementia in older people should be applied when taking care of older people and should be assessed further.